A cross-sectional study on the proper administration of eye medications and its determinants among outpatients attending Brhan Aini Ophthalmic National Referral Hospital in Asmara, Eritrea - Dawit G Weldemariam; Eyasu H Tesfamariam; Nuru Abdu; Alemseghed Goitom Tesfagaber; Tomas Tewelde (BMJ Open, 2024)
Objective This study aimed to assess the administration technique of eye medications, its determinants and disposal practices among ophthalmic outpatients.Design An analytical cross-sectional study was conducted.Setting Brhan Aini Ophthalmic National Referral Hospital in Asmara, Eritrea.Participants Samples of ophthalmic outpatients aged >18 years who visited Brhan Aini Ophthalmic National Referral Hospital in Asmara, Eritrea. Systematic random sampling was used to select the study participants.Data collection and analysis Data were collected from August 2021 to September 2021, using an interview-based questionnaire. The collected data were entered and analysed using CSPro (V.7.3) and SPSS (V.26), respectively. Descriptive statistics and independent samples t-test were performed. P-values less than 0.05 were considered as significant.Results A total of 333 respondents with a mean age of 56.4 (SD: 18.76) years were recruited in the study. More than half of the respondents (57.4%) did not have any information on the time interval between two successive eye medications. However, only 16.5% of the respondents managed to close their tear ducts after the administration of eye medication. The mean (SD) score for proper administration of eye medication was 4.16 (1.07) out of 7.0. Female sex (p=0.002), the absence of glaucoma (p=0.035) and the presence of cataract (p=0.014) were significant determinants of the proper administration technique of eye medication. The most favoured disposal practice for unused and/or expired eye medications was disposing of regular garbage (79.9%).Conclusion This research revealed that there was an inappropriate administration technique and disposal practices of eye medications among ophthalmic outpatients. This requires immediate attention from policy-makers, programme managers and healthcare professionals to ensure the appropriate use of eye medications by the patients.